Effectiveness of physical exercise for people with chronic diseases: the EFIKRONIK study protocol for a hybrid, clinical and implementation randomized trial - María Soledad Arietaleanizbeaskoa; Aintzane Sancho; Iñigo Olazabal; Concepcion Moreno; Erreka Gil; Arturo Garcia-Alvarez; Nere Mendizabal; Ibon de la Fuente; Silvia Dominguez; Susana Pablo; Gonzalo Grandes; on behalf of the EfiKroniK group (BMC Family Practice, 2020)
Abstract Background Chronic illnesses are the leading cause of morbidity and mortality and threaten the sustainability of healthcare systems worldwide. There is limited evidence in terms of the best modality and intensity of physical activity for improving cardiorespiratory capacity and quality of life in patients with chronic conditions. The objective of the EfiKroniK study is to estimate the common effect of innovative, individualized and supervised physical exercise, on cardiorespiratory functional capacity and quality of life across people with different chronic conditions. Methods/design This is a multicentre clinical trial with a type I hybrid effectiveness-implementation design, including 370 patients each with one of four different chronic illnesses: solid cancer, blood cancer, chronic obstructive pulmonary disease or schizophrenia. Patients will be randomly divided into two parallel groups, stratified by illness type. Patients in both groups will receive a standard healthy life prescription (PVS, from the Spanish “Prescribe Vida Saludable”) and additionally, the EfiKroniK group will be prescribed a physical exercise programme tailored to each patient in terms of intensity in each session. The primary outcome variables will be cardiorespiratory functional capacity and quality of life. The secondary outcome variables will be signs and symptoms, psychological and social factors and specific laboratory parameters. We will also analyse the dose-response effect of the physical exercise programme. Qualitative variables will describe patients’ perception of the utility and suitability of the EfiKroniK programme, as well as their expectations and satisfaction, identifying barriers to and facilitators of the EfiKroniK implementation process through discussion groups. The study will be carried out on an intention-to-treat basis, comparing changes throughout the 1-year follow-up between groups, adjusting for baseline, by performing mixed-effect analysis of covariance. We will estimate the effect of time on repeated measures in each subject and changes in the EfiKroniK and PVS groups over time. Discussion The study will provide the data necessary to allow us to prescribe physical exercise in a similar way to a drug and as a key part of the treatment of chronic illnesses within our healthcare system. Trial registration NCT03810755 . Date and version identifier: October 9, 2020. Version2.0.